2004
DOI: 10.2466/pr0.94.3.795-806
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction in Three Countries

Abstract: Studies addressing factors of Life Satisfaction have focused on how individuals in particular societies experience their lives as worthwhile, enjoyable, and fulfilling and indicated a range of individual and cultural factors shape individual perceptions of Life Satisfaction. The purpose of this study was to compare the Life Satisfaction of adults from the United States, Turkey, and Germany. Participants included 163 (84 women and 79 men) from the USA, 172 (70 women, 88 men) from Germany, and 174 (79 women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, the self-described personality traits of people from the Philippines, a collectivist culture, differed from people from North America, an individualist culture (Grimm et al 1999). In terms of well-being, ratings of life satisfaction were higher in the USA than Germany and higher in Germany than Turkey (McConatha et al 2004). Moreover, researchers have suggested that the influence of culture on wellbeing may persist across generations even after a person immigrates to a different continent (Rice and Steele 2004;Veenhoven 1994).…”
Section: Introductionmentioning
confidence: 95%
“…For example, the self-described personality traits of people from the Philippines, a collectivist culture, differed from people from North America, an individualist culture (Grimm et al 1999). In terms of well-being, ratings of life satisfaction were higher in the USA than Germany and higher in Germany than Turkey (McConatha et al 2004). Moreover, researchers have suggested that the influence of culture on wellbeing may persist across generations even after a person immigrates to a different continent (Rice and Steele 2004;Veenhoven 1994).…”
Section: Introductionmentioning
confidence: 95%
“…For example, Diener et al (1995) found that income levels, individualism, and human rights were strong predictors of subjective well-being in different countries. Well-being may also be influenced by such cultural factors as modernization and industrialization, religion, availability of health care, and safety issues within a particular country (McConatha et al 2004). Thus, it should not be assumed that findings among samples in the US necessarily generalize to other cultures.…”
Section: Introductionmentioning
confidence: 98%
“…It examines both to observe whether socio-economic status is a determinant of life satisfaction, and to find out the dimensions of life satisfaction that are discriminating between the individuals of different socio-economic status. McConatha et al (2004) compare the life satisfaction of adults from the United States, Turkey, and Germany. Significant mean differences by country are found on life satisfaction.…”
mentioning
confidence: 99%